Oxidized low‐density lipoprotein (ox‐LDL) promotes cardiac differentiation of bone marrow mesenchymal stem cells via activating ERK1/2 signaling. Issue 6 (27th September 2017) - Zhang, Fenxi; Wang, Congrui; Lin, Juntang; Wang, Xianwei
Summary: Background/Aims: The differentiation efficiency of bone marrow mesenchymal stem cells (BM‐MSCs) is low in vivo after transplantation. Therefore, it is necessary to look for effective reagents for enhancing cardiac differentiation of BM‐MSCs. It has been reported that cardiac differentiation of stem cells depends on the activation of extracellular signal‐regulated protein 1/2 (ERK1/2) signaling. Oxidized low‐density lipoprotein (ox‐LDL) is a potent reagent for ERK1/2 activation. This indicates that ox‐LDL may be a potential reagent to stimulate cardiac differentiation of stem cells. In this study, we investigated the effect of ox‐LDL on cardiac differentiation of BM‐MSCs and its relationship with ERK1/2 signaling. Methods: BM‐MSCs were isolated from mouse bone marrow, cultured in DMEM supplemented with 15% FBS, and passaged up to the 3rd passage. Following culture with 5 μg/mL ox‐LDL for 3 weeks, the cardiac differentiation of the 3rd passage BM‐MSCs was identified by immunostaining, Western blotting, and RT‐PCR assays for measuring the expression of cardiac‐specific markers. To further explore the role of ERK1/2 signaling in cardiac differentiation of BM‐MSCs, we simultaneously exposed BM‐MSCs to ERK1/2 inhibitor (U0126) and ox‐LDL, and identified the cardiac differentiation again. Results: The expressions of cardiac‐specific markers including α‐cardiac actin, α‐MHC, β‐MHC, ANP, and BNP were markedly increased in BM‐MSCs following treatment with ox‐LDL ( P  < .05), which indicates a directional differentiation of BM‐MSCs to cardiac cells. Further, ox‐LDL could also activate ERK1/2 in BM‐MSCs, and application of U0126 markedly inhibited ox‐LDL‐induced cardiac transformation of BM‐MSCs. Conclusions: Ox‐LDL induces cardiac differentiation of BM‐MSCs via activation of ERK1/2 signaling.